Prime Minister's Decree No. 2928 of the year 2022 Amending Certain Provisions of the Executive Regulations of the Law on Joint Stock Companies, Partnerships Limited by Shares, Limited-liability Companies and One-person Companies As Issued by Decree No. 96 of the Year 1982 of the Deputy Prime Minister for Economic and Financial Affairs, and Minister of Investment and International Cooperation Affairs = قرار رئيس مجلس الوزراء رقم 2928 لسنة 2022 بتعديل بعض أحكام اللائحة التنفيذية لقانون شركات المساهمة وشركات التوصية بالأسهم والشركات ذات المسئولية المحدودة وشركات الشخص الواحد الصادرة بقرار نائب رئيس مجلس الوزراء للشئون الاقتصادية والمالية ووزير شئون الاستثمار والتعاون الدولى رقم 96 لسنة 1982 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic